The Role of Digital Citizenship as a Regulator of Academic Ethics in the Era of Disruption: A Systematic Literature Review - Kirana Mentari Fadhillah; M. Faris Sholahuddin Sholeh; Suparmi (Ilmina: Journal of Education and Counseling, 2025)
The rapid development of digital technology has significantly changed academic interactions, creating a digital space that demands the realization of academic ethics in the digital realm. This research is motivated by the gap between the rapid development of technology and low ethical awareness, which has led to cases of integrity violations and unprofessional communication, especially in academic environments. Therefore, this study aims to determine the influence of digital citizenship in implementing academic ethics in the digital space and to formulate the most effective pedagogical strategies for integrating the principles of digital citizenship in order to strengthen academic ethics in the digital space. The method used is a literature review of relevant articles, focusing on articles published in the last 5 years. The results of the analysis show that digital citizenship functions as the main regulator because it provides a moral and legal foundation that encourages self-regulation and prevents cheating. The implementation of digital citizenship has been proven to significantly improve discipline and a culture of integrity.